Conditions Presenting with Symptoms of Peripheral Arterial Disease - Sharma, Aditya M.; Norton, Patrick T.; Zhu, Daisy (Seminars in Interventional Radiology, 2014)
Peripheral artery disease (PAD) is estimated to affect more than 20% of people older than 65 years. The vast majority of patients with symptoms suggestive of PAD have atherosclerosis often associated with conventional vascular risk factors such as smoking, diabetes, dyslipidemia, and inflammation. A minority of people presenting with symptoms suggesting PAD have an alternative etiology. These groups of disorders are often underdiagnosed, and if diagnosed correctly the diagnosis may be delayed. Understanding these pathologies well is important, as they can be very debilitating and optimal treatment may vary significantly. Inappropriate treatment of these disorders can lead to worsening morbidity and mortality. This article discusses the underlying causes of nonatherosclerotic PAD, including the diagnosis and treatment of these disorders.
Keywords: nonatherosclerotic peripheral artery disease; mimics of peripheral vascular disease; iliac artery endofibrosis; popliteal artery entrapment syndrome; fibromuscular dysplasia; interventional radiology